696.DETERMINING THE DEGREE OF ACCEPTABILITY OF THE WORKING BODY POSTURE OF WELDERS THROUGH THE APPLICATION OF THE RULA METHOD - Antonio, Cvetkovski; Sofija, Sidorenko; Elena, Angeleska (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2025)
The purpose of this research is the determination of the degree of ergonomic acceptance of the working body posture of welders in a production plant from the metal processing industry in North Macedonia. The ergonomic analysis is done through the implementation of the Rapid Upper Limb Assessment (RULA) method. The quantitative score of the angles of the joints and working body postures is determined, with added additional scores for overload and muscle activity. Final scores for each welder are compared to four action levels showing the degree of acceptability of the working posture, the level of needed intervention, and a time frame for commencing risk control. The results indicate that welders are exposed to high risk work-related upper extremity musculoskeletal disorders (MSDs). Therefore, proposals for reducing the degree of risk from MSDs are given aimed at adjustments and adaptation of the equipment to the anthropometric characteristics of the individual welders.